Drivers of highly skilled mobility from Southern Europe: escaping the crisis and emancipating oneself. Issue 4 (12th March 2017) - Bartolini, Laura; Gropas, Ruby; Triandafyllidou, Anna
ABSTRACT: Since the outbreak of the crisis in Southern Europe, young highly educated Italians, Spaniards, Portuguese and Greeks have been taking their talents and expertise to other countries in search of a better quality of life and career prospects. This paper explores the characteristics of these new emigrants, the reasons for which they are leaving, and whether these reasons are shaped by the economic crisis, by pre-crisis grievances, or by other factors. We analyse original data from 6377 questionnaires collected in 4 countries through an e-survey we ran in 2013. We refer to the existing literature on the drivers of highly skilled emigration and the (un)employment situation in the four aforementioned Southern European countries which have been hardest hit by the economic crisis. We suggest that while gender is not important, age, marital status, education and satisfaction with current employment (both income related and with regard to future prospects) are important factors predicting emigration. Non-economic factors, notably career opportunities, quality of life and future prospects supersede all other considerations in the decision to emigrate for these highly educated Europeans.